2023
DOI: 10.1021/acsami.2c22911
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Study of Polyvinyl Alcohol Gel Structures with Acrylamide and 2-Acrylamido-2-methyl-1-propanesulfonic Acid for Application in Saline Oil Reservoirs for Profile Modification

Abstract: Polymer gels can be effectively applied to plug fractured reservoirs and carbonate cave strata. Herein, polyvinyl alcohol (PVA), acrylamide, and 2-acrylamido-2-methyl-1-propanesulfonic acid (AMPS) were used as raw materials to prepare interpenetrating three-dimensional network polymer gels using formation saltwater in the Tahe oilfield (Tarim Basin, NW China) as a solvent. The effect of AMPS concentration on the gelation properties of PVA in high-temperature formation saltwater was analyzed. Further, the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…As a main factor for evaluating the hydrogel plugging in the sand pack, the pressure drop accompanying the water injection, showed a sharp increase, followed by a gradual decrease after a peak appeared, and finally, it reached stability for each case (Figure d). As shown in Figure e and Table S1, the breakthrough pressure gradient ( P L ) of the hydrogels reached as high as 63.83–71.56 MPa·m –1 in the sand pack, which was more than four times than that of the chemical crosslinking PVA-based gels (approximately 17 MPa·m –1 ), indicating that the physical PVA–CNF hydrogel possessed an excellent capacity of water controlling. Meanwhile, the hydrogels resided in pores or channels significantly reduced the permeability of the sand pack (nearly 0.2 mD), which produced the fairly high plugging rate (η > 99.9%) and the large residual resistance coefficient (RRF > 2350).…”
Section: Resultsmentioning
confidence: 97%
“…As a main factor for evaluating the hydrogel plugging in the sand pack, the pressure drop accompanying the water injection, showed a sharp increase, followed by a gradual decrease after a peak appeared, and finally, it reached stability for each case (Figure d). As shown in Figure e and Table S1, the breakthrough pressure gradient ( P L ) of the hydrogels reached as high as 63.83–71.56 MPa·m –1 in the sand pack, which was more than four times than that of the chemical crosslinking PVA-based gels (approximately 17 MPa·m –1 ), indicating that the physical PVA–CNF hydrogel possessed an excellent capacity of water controlling. Meanwhile, the hydrogels resided in pores or channels significantly reduced the permeability of the sand pack (nearly 0.2 mD), which produced the fairly high plugging rate (η > 99.9%) and the large residual resistance coefficient (RRF > 2350).…”
Section: Resultsmentioning
confidence: 97%
“…During the above experiment, the injection flow rate of formation saltwater and gelant solution is 1 mL/min. Finally, according to the experimental results, the residual resistance coefficient (RRF), the percentage of permeability reduction (PPR), and the breakthrough pressure gradient ( P L ) are calculated. κ = Q μ L A normalΔ P where κ is the permeability of the simulated core (Darcy), Q is the flow rate (cm 3 /s), μ is the viscosity of saltwater (mPa·s), L is the length of the simulated core (cm), A is the cross-sectional area of the simulated core (cm 2 ), and Δ P is the differential pressure (MPa). RF = normalΔ P gelant 0.25em solution normalΔ P formation 0.25em saltwater where Δ P gelant solution is the differential pressure during gelant solution injection (MPa) and Δ P formation saltwater is the differential pressure during saltwater injection (MPa). RRF = K ωa K ωb PPR = K ωa K ωb K ωa × 100 where K ωa and K ωb are the water injection permeability before and after the gel plugging simulation core. P normalL = P max L where P max is the simulated core of breakthrough pressure after core plugging (MPa) and L is the length of the simulated core (m) …”
Section: Methodsmentioning
confidence: 99%
“…Based on polyvinyl alcohol (PVA) thermal stability, salinity resistance, and biocompatibility, 36,37 Wu et al 38 prepared a PVA/glycerol hydrogel subjected to solvent exchange and wet annealing to reconstruct the hydrogel network structure to achieve a tough, anti-fatigue hydrogel with high chain entanglements and crystallinity; the related PVA products also have certain application prospects in oilfield chemistry. 39−41 In our previous research work, 42 a self-healing PVA composite gel was prepared, and the simulated core displacement device showed that it had better water plugging performance. In this article, PVA and PAM were used as the main agents and HQ and HMTA as a cross-linking system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on total production reserves of well groups, cumulative oil production before gas injection, plane sweep coefficient, irregular pattern shape factor correction, and longitudinal production degree, a calculation method for gas-driven reserves of well groups and well groups under various karst backgrounds is developed [36,37]. The dynamic reserves of fracture-cavity type reservoirs in the Tahe Oilfield, under different fracture-cavity combinations and the influence of bottom water, are calculated and analyzed using production and water injection indicator curves, with the changes in reserves during multiple rounds of production and water injection demonstrated by high-pressure physical models [38,39].…”
Section: Introductionmentioning
confidence: 99%